2020
DOI: 10.1101/2020.05.21.108985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering 6-phosphogluconate dehydrogenase to improve heat tolerance in maize seed development

Abstract: Endosperm starch synthesis is a primary determinant of grain yield and is sensitive to high temperature stress. The maize chloroplast-localized 6-phosphogluconate dehydrogenase (6PGDH), PGD3, is critical for endosperm starch accumulation. Maize also has two cytosolic isozymes, PGD1 and PGD2 that are not required for kernel development. We found that cytosolic PGD1 and PGD2 isozymes have heat stable activity, while amyloplast-localized PGD3 activity is labile under heat stress conditions. We targeted heat-stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…In higher plants, 6PGDH can be divided into cytosolic and plastidic isoforms [16]. We found that Os6PGDH1 has a more closely evolutionary relationship with 6PGDHs of Setaria italica, Sorghum bicolor, and Zea mays, all of which were cytosolic isoforms [18,33,34], confirming that Os6PGDH1 is a cytosolic 6PGDH (Figure 1). Os6PGDH1 was widely expressed in rice tissues but mainly expressed in leaves, outer leaf sheaths, and roots, tissues that are active in anabolic metabolism ( Figure 2); moreover, Os6PGDH1 was induced by mechanical wounding, infestation with gravid BPH females, and JA treatment (Figure 3).…”
Section: Discussionsupporting
confidence: 60%
“…In higher plants, 6PGDH can be divided into cytosolic and plastidic isoforms [16]. We found that Os6PGDH1 has a more closely evolutionary relationship with 6PGDHs of Setaria italica, Sorghum bicolor, and Zea mays, all of which were cytosolic isoforms [18,33,34], confirming that Os6PGDH1 is a cytosolic 6PGDH (Figure 1). Os6PGDH1 was widely expressed in rice tissues but mainly expressed in leaves, outer leaf sheaths, and roots, tissues that are active in anabolic metabolism ( Figure 2); moreover, Os6PGDH1 was induced by mechanical wounding, infestation with gravid BPH females, and JA treatment (Figure 3).…”
Section: Discussionsupporting
confidence: 60%
“…This discovery of identifying and characterizing HSFs and their role in regulating Hsp genes has provided a fundamental basis for the development of GM maize with the highest heat stress tolerance ( Ahuja et al, 2010 ). Furthermore, the overexpression of chloroplast localized 6-phosphogluconate dehydrogenase (6PGDH) PGD3 displayed an over-accumulation of starch in maize endosperm under heat stress improved grain size and weight, whereas, WPGD1 and WPGD2 transgenes can increase the number of kernels to mitigate losses in high nighttime temperature conditions ( Ribeiro et al, 2020 ). In the metabolic studies of Joshi et al (2021) , a total of 5,136 genes expression were affected in response to heat stress.…”
Section: Approaches For Improving Thermotolerancementioning
confidence: 99%
“…Gene 6PGDH has two other isoforms localized in the cytoplasm, PGD1 and PGD2, but, only PGD3 is reported as heat liable (Spielbauer et al, 2013). Subsequently, Ribeiro et al (2020) fused chloroplast targeting peptide sequence, Waxy 1 with pgd1 and pgd2, and found that the fusion proteins, WPGD1 and WPGD2, were complementing PGD3 function resulting in higher grain yield and biomass under high night temperature.…”
Section: Slmentioning
confidence: 99%
“…Subsequently, Ribeiro et al. (2020) fused chloroplast targeting peptide sequence, Waxy 1 with pgd1 and pgd2 , and found that the fusion proteins, WPGD1 and WPGD2, were complementing PGD3 function resulting in higher grain yield and biomass under high night temperature.…”
Section: Exploring Genetic Variation For Heat Stress Tolerancementioning
confidence: 99%